FENOMENA TINGKAT STRES AKADEMIK MAHASISWA KEPERAWATAN DI PEKANBARU - Saniya Saniya; Dea Almira Wahyuni (LPPM Universitas Abdurrab, 2024)
ABSTRACT Background : Academic stress is pressure to achieve better academic activities, for example performance in class, final exam scores, completion of studies and even post-campus life. The prevalence of students experiencing academic stress in Indonesia is 36.7-71.6%. Objective : This study aims to determine the level of academic stress in nursing students in Pekanbaru. Methodology : This type of research uses a descriptive analytical research design using a total sampling technique with a sample size of 128 students using the Perceived Stress Scale (PSS) questionnaire. Data analysis uses univariate analysis to see a descriptive picture. Results : The research results showed that most of the respondents were female, 100 respondents (78.1%) compared to 28 male respondents (21.9%). With the highest results, namely mild stress levels of 80 respondents (62.5%), moderate stress of 45 respondents (35.2%), severe stress of 3 respondents (2.3%). Based on the results of the research conducted, it can be concluded that the description of the stress level of nursing students is at a mild stress level for 80 respondents (62.5%). Suggestion : It is hoped that students can maintain a positive mindset and have good/adaptive coping mechanisms in dealing with stress.